Producing Hot Asphalt Mixtures Using The Natural Asphalt Of Kfaria - احمد, انعام; بسام سلطان, (Latakia University Journal -Engineering Sciences Series, 2023)
The research aims to study the possibility of modifying hot asphalt mixtures using the natural asphalt found in the Kfaria quarry in Lattakia city, with the objective of utilizing the abundant deposits of natural asphalt estimated theoretically at 50 million tons, considering the high cost of petroleum-derived bitumen. The experimental program for this research included the use of bitumen (60-70) with aggregate particles and the addition of a surface asphalt as a modification to the asphalt mixture. The materials used in the design of asphalt mixtures were described, and the necessary experiments were conducted on them to determine the optimal bitumen content according to the Marshall method for the reference mixture. After that, bitumen mixtures were prepared with different percentages of surface asphalt (30%, 40%, 50% of the total mixture weight) along with varying percentages of petroleum asphalt (2%, 2.5%, 3%, 3.5%, 4%) for each mixture. The results showed that replacing 50% of the natural aggregates with Kfaria asphalt met the technical requirements for hot bitumen mixture grade (B). It achieved a stability of 1070 kg, a flow value of 2.4mm, and a density of 2.275 kg/cm3. The optimal asphalt content was determined to be 2.65 according to Marshall Design.